Some Properties of Semi ${}^{#}$ Generalized Open Sets in Topological Spaces - S. Saranya; K. Bageerathi (International Journal of Mathematics And its Applications, 2017)
In this paper a new class of generalized open sets in topological spaces, namely semi ${}^{#}$ generalized open(briefly, $s^{#}$g-open) sets is introduced. We prove that this class lies between the class of sg-open sets and the class of gs-open sets and we study some basic properties and characterizations of $s^{#}$g-open sets. Also we introduce $s^{#}$g-neighbourhood (shortly, $s^{#}$-neighbourhood), $s^{#}$g-interior, $s^{#}$g-closure and $s^{#}$g-derived set of a set in a topological spaces and investigate some basic properties of these sets.